1972
DOI: 10.1111/j.1467-1770.1972.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Dictation as a Measure of Mutual Intelligibility: A Pilot Study

Abstract: An experiment using dictation in foreign and native accents of English suggests that this is a fruitful device for the study of individual and group differences affecting mutual intelligibility. P r i o r listener-experience with the voice of the speaker appears to be a prominent factor in intelligibility, indicating that accommodation to the speaker over time is a crucial variable, and that languaqe teachers are a p t to be the poorest judges of their students' ability to communicate with strangers. A combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 3 publications
1
30
0
Order By: Relevance
“…As reported in Munro et al (2006), Flege (1998) Sometimes speech perceived as heavily accented is also perceived as completely comprehensible and intelligible (Brodkey, 1972;Derwing & Munro, 1997;Munro & Derwing, 1995;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), thus, "listeners often assign good comprehensibility ratings to speech samples that they have also rated as heavily accented" (Derwing & Munro, 2005, p. 386). Results only show that listeners from different L1 backgrounds can equally recognize that accents are there.…”
Section: Accent Familiarity and Ratingmentioning
confidence: 98%
“…As reported in Munro et al (2006), Flege (1998) Sometimes speech perceived as heavily accented is also perceived as completely comprehensible and intelligible (Brodkey, 1972;Derwing & Munro, 1997;Munro & Derwing, 1995;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), thus, "listeners often assign good comprehensibility ratings to speech samples that they have also rated as heavily accented" (Derwing & Munro, 2005, p. 386). Results only show that listeners from different L1 backgrounds can equally recognize that accents are there.…”
Section: Accent Familiarity and Ratingmentioning
confidence: 98%
“…Some research has shown that familiarity with the speaker's accent facilitates comprehension and may thus lead to more lenient evaluations of the overall speech quality (Brodkey, 1972;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979), whereas other studies have revealed lower tolerance of their peers' speech by nonnative speakers of the target second language (L2) than native speakers (Fayer & Krasinski, 1987;Sheorey, 1985). These conflicting findings may be partially due to differences in whether naive or trained raters are used, how adequately the raters are trained, and whether the raters undergo rigorous certification requirements.…”
Section: Executive Summarymentioning
confidence: 99%
“…Some research has shown that familiarity with the speaker's accent may lead to more lenient evaluations of the overall speech quality (Brodkey, 1972;Gass & Varonis, 1984;Smith & Bisazza, 1982;Smith & Rafiqzad, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…This objective measure of speech intelligibility contrasts with other measures in which listeners subjectively rate the "intelligibility" of a speaker ͑also called comprehensibility; e.g., Fayer and Krasinski, 1987͒ or tests in which the listener must provide an accurate paraphrase of the talker's message for the talker's communicative intent to be considered effective ͑e.g., Brodkey, 1972͒. …”
mentioning
confidence: 99%